Optimising modern wound care to improve the quality of life and self-confidence of patients with diabetes mellitus - Fatmawati Fatmawati; Barangkau Barangkau; Yammar Yammar; Asnuddin Asnuddin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diabetes Mellitus (DM) remains a prevalent global health challenge, with significant incidence rates observed in Indonesia, particularly within South Sulawesi. Current data records 10.64 million cases in 2024, with projections estimating a rise to 40.7 million by 2045. A substantial number of these patients suffer from diabetic ulcers, a complication that severely compromises quality of life and self-confidence. Purpose: To evaluate the efficacy of optimized modern wound care interventions in enhancing the quality of life and self-confidence of patients with Diabetes Mellitus. Method: A pre-experimental design. A total sampling technique was employed to select 25 registered DM patients at the Masagena Independent Wound Care Practice. Statistical analysis was conducted using paired t-tests with a significance threshold of p < 0.05. Results: The analysis revealed significant differences in patient outcomes following the intervention (p < 0.05). The mean quality of life score improved markedly from a baseline of 8.72 ± 2.85 to 94.20 ± 3.41 post-intervention. Similarly, the mean self-confidence score increased from 8.36 ± 2.69 (pre-test) to 93.92 ± 2.88 following the implementation of modern wound care optimization. Conclusion: The optimization of modern wound care significantly positively impacts type 2 DM patients, resulting in a demonstrated increase in both quality of life and self-confidence.